Patients with tumour necrosis factor (TNF) receptor‐associated periodic syndrome (TRAPS) are hypersensitive to Toll‐like receptor 9 stimulation. (22nd May 2019) - Negm, O. H.; Singh, S.; Abduljabbar, W.; Hamed, M. R; Radford, P.; McDermott, E. M.; Drewe, E.; Fairclough, L.; Todd, I.; Tighe, P. J.
Summary: Tumour necrosis factor receptor‐associated periodic syndrome (TRAPS) is a hereditary autoinflammatory disorder characterized by recurrent episodes of fever and inflammation. It is associated with autosomal dominant mutations in TNFRSF1A, which encodes tumour necrosis factor receptor 1 (TNF‐R1). Our aim was to understand the influence of TRAPS mutations on the response to stimulation of the pattern recognition Toll‐like receptor (TLR)‐9. Peripheral blood mononuclear cells (PBMCs) and serum were isolated from TRAPS patients and healthy controls: serum levels of 15 proinflammatory cytokines were measured to assess the initial inflammatory status. Interleukin (IL)‐1β, IL‐6, IL‐8, IL‐17, IL‐22, tumour necrosis factor (TNF)‐α, vascular endothelial growth factor (VEGF), interferon (IFN)‐γ, monocyte chemoattractant protein 1 (MCP‐1) and transforming growth factor (TGF)‐β were significantly elevated in TRAPS patients' sera, consistent with constitutive inflammation. Stimulation of PBMCs with TLR‐9 ligand (ODN2006) triggered significantly greater up‐regulation of proinflammatory signalling intermediates [TNF receptor‐associated factor (TRAF 3), IL‐1 receptor‐associated kinase‐like 2 (IRAK2), Toll interacting protein (TOLLIP), TRAF6, phosphorylated transforming growth factor‐β‐activated kinase 1 (pTAK), transforming growth factor‐β‐activated kinase‐binding protein 2 (TAB2), phosphorylated TAK 2 (pTAB2), IFN‐regulatory factor 7 (IRF7), receptor interacting protein (RIP), nuclear factor kappa B (NF‐κB) p65, phosphorylated NF‐κB p65 (pNF‐κB p65) and mitogen‐activated protein kinase kinase (MEK1/2)] in TRAPS patients' PBMCs. This up‐regulation of proinflammatory signalling intermediates and raised serum cytokines occurred despite concurrent anakinra treatment and no overt clinical symptoms at time of sampling. These novel findings further demonstrate the wide‐ranging nature of the dysregulation of innate immune responses underlying the pathology of TRAPS and highlights the need for novel pathway‐specific therapeutic treatments for this disease. Abstract : Stimulation of TRAPS patient PBMCs with TLR‐9 ligand (ODN2006) triggers significantly greater up‐regulation, relative to controls, of proinflammatory signalling intermediates TRAF3, IRAK2, TOLLIP, TRAF6, pTAK, TAB2, phosphorylated TAB2 (pTAB2), IRF7, RIP, NF‐κB p65, phosphorylated NFκB p65 and MEK1/2. This up‐regulation of proinflammatory signalling intermediates and raised serum cytokines occurred despite concurrent anakinra treatment and no overt clinical symptoms at time of sampling. These novel findings further demonstrate the wide‐ranging nature of the dysregulation of innate immune responses underlying the pathology of TRAPS.